2011
DOI: 10.1002/jgm.1575
|View full text |Cite
|
Sign up to set email alerts
|

Adeno‐associated virus‐mediated expression of acid sphingomyelinase decreases atherosclerotic lesion formation in apolipoprotein E−/− mice

Abstract: Unexpectedly, the lesion area of the entire aorta was reduced significantly in the AAV8-ASM virus-treated group. Hepatic expression and secretion of ASM into the circulation did not accelerate or exacerbate, but rather decreased, lesion formation in ApoE(-/-) mice. Thus, plasma ASM activity does not appear to be rate limiting for plaque formation during atherogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Plaque formation in the aortic sinus after 17 weeks did not differ in mice treated with a control AAV. These findings suggest that S-ASM has no accelerating or exacerbating role in atherosclerotic lesion formation in the ApoE -/-model of atherosclerosis (Leger et al, 2011).…”
Section: S-asm and Atherosclerosismentioning
confidence: 72%
See 1 more Smart Citation
“…Plaque formation in the aortic sinus after 17 weeks did not differ in mice treated with a control AAV. These findings suggest that S-ASM has no accelerating or exacerbating role in atherosclerotic lesion formation in the ApoE -/-model of atherosclerosis (Leger et al, 2011).…”
Section: S-asm and Atherosclerosismentioning
confidence: 72%
“…Feeding rats grape seed oil vs. butter leads to increased S-ASM activity and, simultaneously, decreased ceramide concentrations (Drachmann et al, 2007). The induction of S-ASM activity by adeno-associated virus in ApoE -/-mice resulted in only minor changes in SM and ceramide: a small reduction of SM and ceramide in plasma at several time points after injection and a reduction of SM and unaltered ceramide concentrations in the liver (Leger et al, 2011). Correlations between S-ASM in plasma SM and ceramide were previously reported only sporadically (Sathishkumar et al, 2005).…”
Section: In Vivo Effects Of S-asm Activity On Sphingolipid Levelsmentioning
confidence: 99%
“…For en face analysis, aortas were split longitudinally ( 27 ). Sections and fi xed aortas were stained with Oil Red O (ORO) for 30 min and rinsed ( 28 ). Images of the ORO staining sections and the open luminal surface of the vessels were captured with a Leica Q550cw Graphic Analysis System and a digital camera (Sony), respectively.…”
Section: Analysis Of Atherosclerosis In Atherosclerotic Micementioning
confidence: 99%
“…The pooling of ASM in secretory lysosomes seems to participate in signal transduction events; however, the precise role of ASM in the development of atherosclerosis remains unclear. Secretory ASM may be atherogenic, whereas the lysosomal form of ASM may have anti-atherogenic effects[2-5]. Previous studies demonstrated that the atherogenic action of secretory ASM in the plasma may be mainly associated with ceramide-promoted lipoprotein aggregation or uptake by arterial-wall macrophages that leads to foam cell formation[5-6].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that the atherogenic action of secretory ASM in the plasma may be mainly associated with ceramide-promoted lipoprotein aggregation or uptake by arterial-wall macrophages that leads to foam cell formation[5-6]. However, a recent study demonstrated that adenovirus-mediated expression and secretion of ASM into the circulation did not exacerbate but decreased lesion formation in atherosclerotic ApoE −/− mice, indicating that plasma ASM activity may not be determinant for plaque formation during atherogenesis[2]. In another aspect, lysosomal ASM activity can be anti-atherogenic since it increases sphingomyelin hydrolysis reducing accumulation of cholesterol in lysosome of macrophages given that sphingomyelin has high binding affinity to cholesterol[7-8].…”
Section: Introductionmentioning
confidence: 99%